Władysław Wojciech Wrześniowski (1865–1940). Portrait of a provincial doctor - Czerniecka‑Haberko, Anna (Marginesy, 2021)
Dr Władysław Wrześniowski came from Warsaw. He was born and received his education in this city. However, his whole professional life was connected with Częstochowa. In 1896, dr Władysław Biegański offered dr Wrześniowski a post of a junior consultant in a municipal hospital. Already the following year, after the resignation of dr Biegański, dr Wrześniowski took over as the chief hospital physician. He stayed in the office till 1933, i.e. his retirement. The hospital was reconstructed and equipped under the supervision of dr Wrześniowski. In 1932, the hospital was granted the status of surgery hospital. Dr Wrześniowski developed the statute and regulations of this hospital. Dr Wrześniowski was a talented surgeon. He performed a wide range of operations. They varied from general surgeries, laryngological surgeries, urological surgeries to gynaecological ones. He was engaged in the activity of many medical organizations, such as the Częstochowa Medical Association, the Cracow Medical Chamber, the Association of Polish Physicians. What is more, he devoted his time to various initiatives of the Częstochowa intelligentsia.